2011
DOI: 10.2298/vsp1108684o
|View full text |Cite
|
Sign up to set email alerts
|

Low power laser efficacy in the therapy of inflamed gingive in diabetics with parodontopathy

Abstract: Low level laser therapy is efficient in gingival inflammation elimination and can be proposed as an adjuvant tool in basic periodontal therapy of diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although lasers have no defined and accepted protocols for standard usage, the most commonly recommended doses are from 1 to 10 J/cm 2 per treatment . Coordinated standpoints are necessary to allow easier application of LLLT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lasers have no defined and accepted protocols for standard usage, the most commonly recommended doses are from 1 to 10 J/cm 2 per treatment . Coordinated standpoints are necessary to allow easier application of LLLT .…”
Section: Discussionmentioning
confidence: 99%
“…Obradovic et al also found a significant decrease in the size of nuclei of the stratified squamous epithelial cells after SRP treatment of chronic periodontitis ( P < .05). This decrease was even more pronounced after LLLT + SRP treatment ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Cell desquamation of stratified squamous epithelium depends on mitotic action of a basal layer, enzyme activity in cell culture and action of mechanical irritation (13). Obradović et al (15) showed that during the gingival inflammation, which is common in diabetic patients, there were deviations in size and shape of cells of stratified aqueous epithelium , and that increased their nuclei regardless of the degree of differentiation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental shock wave studies report similar results (26,27,28). In comparison, laser therapy also offers very good results, including in diabetic patients, with respect to alveolar bone regeneration, providing a radiological appearance similar to the use of pulsed short waves assessed at one year (29,30).…”
Section: A B Cmentioning
confidence: 59%